The Cascade device – In vitro tests to assess coil protrusion into the parent vessel. Issue 4 (August 2020) - Bhogal, P; Wong, K; Makalanda, HLD
Background: Balloon and stent-assisted coiling of aneurysms have increased the number of aneurysms available for endovascular treatment. Newer devices that allow flow within the parent vessel but coverage at the neck have recently entered the market. The Cascade is a new non-occlusive fully retrievable neck-bridging support device that has been designed to provide temporary support during coil embolisation of intracranial aneurysms. Methods: Using a silicone aneurysm model three different aneurysms were catheterised with the coiling microcatheter placed in three different positions within each aneurysm – at the neck, centrally, and looped within the aneurysm. Multiple different coils were then deployed within each aneurysm with the Cascade device deployed across the neck to provide protection. In total 480 attempted coilings were performed. Aneurysm flow was used to calculate the change in intra-aneurysmal flow with the Cascade device deployed across the neck of the aneurysm. Results: We did not observe a single episode of coil protrusion through the Cascade mesh nor did we observe any coil protrusion into the parent vessel when the Cascade was deployed across the neck. There was an average flow velocity reduction of 23% with the Cascade device deployed across the neck of the aneurysm. Conclusion: The Cascade device offers robust protection of the aneurysmal neck and parent vessel as well as inducing significant intra-aneurysmal flow velocity reduction.